Building A Specialised Multilingual Dictionary From General Monolingual Dictionaries. - Chuah, Choy Kim (2004)
There have been efforts to link entries to produce an "enriched" bilingual or even multilingual dictionary. To do this. we mainly make use of the definition of the dictionary. In this paper, we report how we can easily prepare the first draft of a specialised dictionary of plants/animals from two monolingual dictionaries.